BOSHLANG‘ICH TA’LIMDA O‘QUVCHILAR IJODIY FAOLIYATINI SHAKLLANTIRISH YO‘LLARI - Xurramov, R. (SCIENCE and SOCIETY, 2023)
We all know that the creative cognitive activity of elementary school students includes stable motivations for acquiring new knowledge and a positive emotional orientation to the cognitive process, which helps to eliminate the usual methods of educational behavior in solving educational tasks. reflects the character of a person characterized by aspiration, search for non-standard methods and methods of finding a solution to a problem, persistence in learning and learning activities, effectiveness of creative cognitive activities. This article is intended for university students, doctoral students, independent researchers and a wide audience.